Blue Amino Acids Derived from Azulen-1-ylboronic Acid Pinacol Ester via the Petasis Reaction - Murafuji, Toshihiro; Tasaki, Yusuke; Fujinaga, Masayuki; Tao, Keisuke; Kamijo, Shin; Ishiguro, Katsuya (Synthesis, 2017)
Azulen-1-ylboronic acid pinacol ester undergoes a three-component Petasis reaction with amines and glyoxylic acid hydrate to give azulenylglycine derivatives in good yields. The progress of the reaction is indicated by a characteristic color change from violet to blue due to the altered π-conjugation of the azulene chromophore. The azulenylboronic ester is more reactive than its phenyl counterpart and even 2-styryl- and 2-thienylboronic pinacol esters, which have a strong electron-donating organyl group on boron. These results reflect the unique π-electron system of non-alternant azulene.
Keywords: amino acids; azulene; boron; multicomponent reactions; Petasis reaction